PENGARUH RASIO KEUANGAN TERHADAP INVESTMENT OPPORTUNITY SET DALAM TAHAPAN SIKLUS HIDUP PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2006-2010 - PURNAMA SARI, MARIA AGNES INDRI (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Investment Opportunity Set (IOS) is an opportunity or an investment opportunity for a company. The investment opportunities of a company can be seen through the financial performance of companies that have different proportions at each stage of the life cycle firms. Therefore this research aims to examine and analyze the effect of financial ratios giving of the investment opportunity set in the stage of the life cycle of manufacturing firms. The research design was quantitative with the hypothesis. Type of data is quantitative. Data sources from Indonesian Capital Market Directory. Variabel used includes IOS which measured by the IOS based on investment and financial ratios as measured by the liquidity ratio, profitability ratio, activity ratio, solvency ratio. Sample used is a manufacturing fims listed in indonesia stock exchage in 2006-2010 as many as 140 firms. Data analysis techniques using miltiple linier regression. Analyticaly result of this study is on the establishment stage only the liquidity and activity ratios has effect on IOS. In the initial expansion stage no ratios has effect on IOS, while on the final expansion stage only profitability ratios has effect on IOS. At the stage of maturity only profitability and solvency ratios has effect on IOS. On the decline stage only the profitability ratios has effect on IOS.